Observed CD4 counts at entry into HIV care and at antiretroviral therapy prescription by age in the USA, 2004–18: a cohort study. (March 2022) - Lee, Jennifer S; Humes, Elizabeth; Hogan, Brenna C; Justice, Amy C; Klein, Marina; Gebo, Kelly; John Gill, M; Silverberg, Michael J; Rebeiro, Peter; Horberg, Michael; Karris, Maile; Rabkin, Charles; et al.
Summary: Background: Adults aged 50 years or older comprise a majority of people with HIV in the USA. Our objective was to describe observed differences by age in CD4 count at entry into HIV care, timing of antiretroviral therapy (ART) prescription, and CD4 count at time of ART prescription before (2004–11) and during (2012–18) the current era of universal treatment. Methods: For this descriptive study, we calculated median (IQR) CD4 count at entry into care, days from entry into care to ART prescription, and CD4 count at time of ART prescription among patients enrolled in US-based clinical cohorts of the North American AIDS Cohort Collaboration on Research and Design (NA-ACCORD; see appendix ). We excluded participants with no CD4 count recorded at entry into care, medical records that suggested previous ART use, or previous AIDS diagnosis. All calculations were stratified by age (≥50 and 18–50 years) and calendar year. Findings: Of 35 293 ART-naive adult participants entering care between Jan 1, 2004 and Dec 31, 2018, 5794 (16%) were women and 29 499 (84%) were men; 15817 (45%) were Black, 11566 (33%) were White, 5538 (16%) were Hispanic (any race), 737 (2%) were Asian or Pacific Islander, 152 (0.4%) were Indigenous, and 98 (0.3%) were multiracial. Median age at entry into care was 39 years (IQR 29–49); 8004 (23%) were aged 50 years or older. Of 29 141 participants initially prescribed ART, 7274 (25%) were aged 50 years or older. From 2004 to 2018, median CD4 count at entry into care increased from 228 cells per µL (IQR 80–422) to 295 cells per µL (134–489) among adults aged 50 years and older, and from 297 cells per µL (119–480) to 378 cells per µL (202–564) among adults younger than 50 years. Median days from entry into care to ART prescription declined from 56 (IQR 17–658) to 6 (0–15) among adults older than 50 years, and from 61 (17–509) to 6 (0–16) among adults younger than 50 years. Median CD4 count at time of ART prescription increased from 139 cells per µL (IQR 59–257) to 311 cells per µL (137–504) among adults aged 50 years or older, and from 166 cells per µL (49–287) to 377 cells per µL (198–564) among adults younger than 50 years. Interpretation: Before the release of universal treatment guidelines by the US Department of Health and Human Services in 2012, median time to ART prescription was already falling, leading to increases in median CD4 count at ART prescription for both age groups; both measures continued to improve in the treat-all era. However, median CD4 counts, both at entry into care and at ART prescription, among adults aged 50 years and older were lower than those of adults younger than 50 years throughout the study period. Furthermore, even into the treat-all era, over half of adults aged 50 years and older entered care with CD4 counts of less than 350 cells per µL, potentially because of factors including immunosenescence, delayed HIV diagnosis, and late presentation to care. Given that age-related immunological changes might not be fully avoidable, targeted strategies for increasing HIV risk awareness, routine testing, and immediate linkage to HIV care at diagnosis are particularly essential for this population. Funding: US National Institutes of Health grant U01AI069918.